Luteolin Inhibits Listeriolysin O Translation by Directly Targeting the Coding Region of the hly mRNA - Wang, Jianfeng; Liu, Shui; Liu, Bowen; Niu, Xiaodi; Deng, Xuming (Frontiers in Microbiology, 2019)
Listeriolysin O (LLO) is important for bacterial escape from the phagosome into the cytoplasm, which suggests that targeting LLO may be an alternative strategy to combat L. monocytogenes-mediated infection. Here, luteolin, a natural compound without anti-bacterial activity, as indentified as effective inhibitor of LLO by translationally inhibiting the production of LLO. Additionally, luteolin-treated L. monocytogenes displayed reductions in cytoplasmic growth, cytotoxicity and phagosome escape within macrophages. Molecular modeling and mutational analysis revealed a direct interaction between luteolin and the 5' coding region (A818, U819, G820 and U830 located in nt 814-849) of the mRNA of hly, the gene encoding LLO, which interfered with its translation. Together, our data demonstrate that luteolin may be used as a novel therapeutic and lead compound for treating L. monocytogenes infection.